Enhancing Digitally-Mediated Human-Centred Design With Digitally-Mediated Community Based Participatory Research Approaches for the Development of a Digital Access-to-Justice Platform for Military Veterans and Their Families - Olaoluwa Olusanya; William G.A. Collier; Simon Marshall; Victoria Knapp; Alex Baldwin (Journal of Participatory Research Methods)
Before the COVID-19 crisis, in-person engagement was the main method of ensuring community participation in participatory research processes. However, the pandemic accelerated the switch to digitally-mediated participatory research methods (DMPRMs). This article presents a case study of a digitally-mediated, human-centered design (DMHCD) process enhanced by digitally-mediated community-based participatory research approaches (DMCBPR) as part of our efforts to develop a digital access-to-justice platform for military veterans and their families. We reflect on our experience of enhancing DMHCD with DMCBPR approaches and include insights about how to facilitate the transition from in-person HCD+CBPR to DMHCD-DMCBPR. We also discuss the dual challenges of combining two different approaches while shifting to a virtual/online participatory research framework. Finally, the present study aims to achieve the following objectives: first, to add to a small---but growing---body of research around digitally-mediated participatory research methods; and second, to add to the emerging literature on HCD+CBPR integration approaches to design interventions for underserved populations.